Molecular dynamics simulation of thermodynamic and transport properties of H-bonded low-temperature substances - Tychengulova, A. J.; Aldiyarov, A. U.; Drobyshev, A. S. (Хабаршы. Физика сериясы, 2015)
The results of modeling of water clusters in nitrogen cryomatrix are presented. Earlier, our experimental studies of water in cryomatrix [1] have shown that changes in the concentration of an analyte in matrixleads to a splitting of the absorption bands characteristic frequencies of the molecules in the IR spectrum. Moreover the multiplicity of characteristic absorption bands in the IR spectrum remained unchanged during heating of the samples from the condensation temperature to the sublimation temperature of the matrix element.